2005
DOI: 10.1196/annals.1313.033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Anti‐CCP Assay: Experiences with 700 Patients

Abstract: Our objective was to determine the frequency of antibodies to cyclic citrullinated peptides (CCPs) in a series of patients with a variety of rheumatic diseases. Seven hundred consecutive serum samples from patients at an outpatient clinic were tested for the presence of rheumatoid factor (RF) and anti-CCP. Clinical diagnosis, radiographic information, and other laboratory data were taken from patients' charts. The sensitivity and specificity of anti-CCP reactivity for the diagnosis of rheumatoid arthritis (RA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 8 publications
2
35
2
5
Order By: Relevance
“…These antibodies are thought to be triggered by the genes that increase susceptibility to RA as well as by many environmental agents. [3] The anti-cyclic citrullinated peptide (anti-CCP) has a comparable sensitivity to RF (50-75%) with a higher specificity (90-95%) [3,5] and is the new candidate for the crown of RF. Along with anti-CCP, there has been interest in another new marker, anti-mutated citrullinated vimentin (anti-MCV).…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies are thought to be triggered by the genes that increase susceptibility to RA as well as by many environmental agents. [3] The anti-cyclic citrullinated peptide (anti-CCP) has a comparable sensitivity to RF (50-75%) with a higher specificity (90-95%) [3,5] and is the new candidate for the crown of RF. Along with anti-CCP, there has been interest in another new marker, anti-mutated citrullinated vimentin (anti-MCV).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of anti-CCP antibodies for RA has been established in several studies including other autoimmune and infectious diseases (16,(18)(19)(20)(21)(22)(23). This is the first study designed to evaluate anti-CCP antibodies in a large number of leprosy patients either with (N = 76) or without (N = 82) articular involvement.…”
Section: Sle Ribeiro Et Almentioning
confidence: 99%
“…Anti-CCP antibodies have been evaluated in a large number of patients with different autoimmune (16,(18)(19)(20)(21) and infectious diseases (16,(21)(22)(23)(24). More recently, a high frequency (32%) of anti-CCP antibodies was reported in patients with active lung tuberculosis (24) and another study showed a low frequency of anti-CCP among patients with leprosy, a disease caused by another mycobacterium (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic CCP variants react with anti-ilaggrin autoantibodies and serve as substrate for detecting anti-CCP antibodies serologically 6 . The sensitivity of anti-CCP is about 74% and the speci icity is 96% to 98%, as compared to RF whose sensitivity and speci icity are 69.7% and 81%, respectively 7 . Hence, anti-CCP assay is a more speci ic and powerful serologic marker for diagnosing RA.…”
Section: Discussionmentioning
confidence: 99%